(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Toxic responses of distilled water, 50% ethyl and absolute ethyl alcohol extracts of six indigenous plants, Datura innoxia (Mill), Clerodendrum viscosum (Vent), Amoora rohituka (Roxb) Wt. et. Arnott, Acacia auriculaeformis A. Cunn. ex. Benth., Pongamia pinnata (L) Pierre and Acacia catechu Willd were studied on a predatory fish Heteropneustes fossilis (Bloch) in laboratory conditions. Amongst the extracts the toxicity range varied, absolute ethyl alcohol extract of A. rohituka seeds being the most toxic (LC50 = 8.67 ppm) whilst distilled water extract of D. innoxia seeds was the least toxic (LC50 = 1950.03 ppm). On the basis of LC50 and relative potency values the relative toxicity of the six plants was in the order- A. rohituka > C. viscosum > P. pinnata > A. auriculaeformis > A. catechu > D. innoxia seed extracts. These six indigenous plant seed extracts assayed might be helpful as controlling agent of undesirable fishes in fish culture ponds. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13382 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):1-12, 2009